Knowledge–Behavior GAP pada Perilaku Pro-Lingkungan Mahasiswa Pendidikan Akuntansi: Bukti dari Model Mediasi Sikap Lingkungan - Shinta Puspitasari; Ahmad Nurkhin; Algifari (MIZANIA: Jurnal Ekonomi Dan Akuntansi, 2026)
Despite students' relatively high levels of environmental knowledge, pro-environmental behavior remains inconsistent. This condition indicates a knowledge–behavior gap influenced by psychological factors, particularly environmental attitude. This study aims to analyze the effect of environmental accounting knowledge and environmental knowledge on pro-environmental behavior, with environmental attitude as a mediating variable. A quantitative causal design was applied to 184 accounting education students at the Faculty of Economics and Business, Semarang State University, selected through proportionate stratified random sampling. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. Results showed that environmental accounting knowledge has no direct effect on pro-environmental behavior, whereas environmental knowledge and environmental attitude have significant positive effects. Environmental accounting knowledge influences environmental attitude, but environmental attitude does not mediate its relationship with pro-environmental behavior. Conversely, environmental attitude partially mediates the relationship between environmental knowledge and pro-environmental behavior. These findings suggest that developing students' pro-environmental behavior requires not merely conceptual environmental accounting knowledge, but deep internalization of environmental knowledge capable of forming positive environmental attitudes. This study contributes to extending the application of the Theory of Planned Behavior in explaining the mechanism of pro-environmental behavior formation in accounting education contexts.